The Nucleosome Remodelling and Deacetylation complex suppresses transcriptional noise during lineage commitment. (29th April 2019) - Burgold, Thomas; Barber, Michael; Kloet, Susan; Cramard, Julie; Gharbi, Sarah; Floyd, Robin; Kinoshita, Masaki; Ralser, Meryem; Vermeulen, Michiel; Reynolds, Nicola; Dietmann, Sabine; Hendrich, Brian
Abstract: Multiprotein chromatin remodelling complexes show remarkable conservation of function amongst metazoans, even though components present in invertebrates are often found as multiple paralogous proteins in vertebrate complexes. In some cases, these paralogues specify distinct biochemical and/or functional activities in vertebrate cells. Here, we set out to define the biochemical and functional diversity encoded by one such group of proteins within the mammalian Nucleosome Remodelling and Deacetylation (NuRD) complex: Mta1, Mta2 and Mta3. We find that, in contrast to what has been described in somatic cells, MTA proteins are not mutually exclusive within embryonic stem (ES) cell NuRD and, despite subtle differences in chromatin binding and biochemical interactions, serve largely redundant functions. ES cells lacking all three MTA proteins exhibit complete NuRD loss of function and are viable, allowing us to identify a previously unreported function for NuRD in reducing transcriptional noise, which is essential for maintaining a proper differentiation trajectory during early stages of lineage commitment. Synopsis: The biochemical and functional diversity between Mta1, Mta2 and Mta3, three paralogous constituents of the conserved NuRD chromatin remodeler, remains open. This work finds them to be functionally redundant and non‐essential in mouse ES cells, and reveals a new NuRD function in preventing transcriptional noise and instructing lineage identity. MTA proteins are not mutually exclusive within NuRD, and are functionally redundant in ES cells. ES cells lacking all three MTA proteins are viable, representing the first complete NuRD loss‐of‐function model system. Complete NuRD‐null ES cells reveal a novel function for the complex in suppressing transcriptional noise. NuRD‐mediated repression ensures an appropriate cell trajectory during differentiation, thus contributing to normal development. Abstract : Paralogous NuRD chromatin remodeler components Mta1, Mta2, and Mta3 are functionally redundant and non‐essential in mouse ES cells, but required for transcriptional repression to ensure appropriate lineage specification.